Potensi Risiko Penyebaran Kasus Demam Berdarah Dengue di Jakarta Pusat - Vanny Narita (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2011)
Dengue Hemorrhagic Fever (DHF) caused by four virus serotypes is a disease with A. aegyti and A. albopictus mosquitoes as vectors. DHF is a recurrent and high burdened disease in Indonesia. The purpose of this study is to analyze the spreading of DHF risk in Central Jakarta based on environmental factors. The cases number data year 2000-2009 was obtained from Center of Infectious Disease Research, National Institute of Health in Research and Development. Survey was performed in 38 subdistricts using random and purposive methods. Risk indicators were used in environmental data collection. The results of this study showed similar cyclical pattern each year.  March until May had a high DHF incident, while November until January had a relatively low DHF incident. In general, Central Jakarta had a medium risk potential of DHF spreading. Spearman rank analysis on adjacent areas gave various values. Subdistricts of Senen and Kemayoran had a low correlation, while subdistricts of Johar Baru and Cempaka Putih had the highest correlation among other subdistricts showing that there were vector migrations between these two subdistricts. Finally, the data obtained should be useful for minimalizing the risk of DHF spreading especially by vector control management.